A brief report of aspiring medical student perceptions and behaviours concerning research experiences for selection into Canadian medical schools - Chang, Irene; Yang, Laurie; Elma, Asiana; Ritz, Stacey A; Grierson, Lawrence (Canadian Medical Education Journal / Revue canadienne de l'éducation médicale)

(untitled) (Canadian Medical Education Journal, 2023)
Background: Aspiring medical students behave based on their perception of what is valued in the selection process. While research experience is not explicitly considered in most Canadian admissions policies, it is commonly held as valuable within aspiring medical student communities. The purpose of this study is to describe the perceptions and behaviours of aspiring medical students with respect to gaining research experience in support of their medical school applications.Methods: We surveyed prospective applicants of Canadian medical schools between August 2021 and November 2021, then compiled descriptive statistics pertaining to their perceptions and behaviours.Results: Respondents affirmed the belief that research experience is valued in medical school admissions processes. They reported spending approximately 13 hours per week engaged in research, which usually did not yield publication or presentation recognition.Conclusion: Aspiring medical students invest substantial time and energy in research experiences to benefit their applications. There is room for medical schools to be more transparent about the value of research experience in their admissions processes.